Influence of denture surface roughness and host factors on dental calculi formation on dentures: a cross-sectional study - Keisuke Matsumura; Yuji Sato; Noboru Kitagawa; Toshiharu Shichita; Daisuke Kawata; Mariko Ishikawa (BMC Oral Health, 2018)
Abstract Background Dental calculi formation on dentures can worsen the oral cavity environment by complicating oral hygiene. However, few studies have investigated the effect of how patients use and manage their dentures, denture surface roughness, and host factors such as oral cavity dryness and saliva properties on denture cleanliness and denture dental calculi formation. Accordingly, we conducted the present survey to evaluate these factors to clarify the strength of the influence of each factor. Methods We enrolled 53 patients who had used dentures for at least 3 months and used a dental prosthesis that covered at least the six front teeth including the left and right mandibular canines. After staining the dentures, we divided the participants into a group that was positive for dental calculi (DCP group) and a group that was negative for dental calculi (DCN group). After removing all the stains, we evaluated the surface roughness of the dentures. A questionnaire was used to survey how the participants used and managed their dentures. Oral cavity dryness was evaluated, and resting saliva samples were collected to assess saliva properties. Correlations between the presence or absence of dental calculi and denture use and management were evaluated using a chi-square test. Correlations with denture surface roughness, oral cavity dryness, and saliva properties were evaluated using the Mann–Whitney U test. Correlations between the presence or absence of dental calculi and all factors were analyzed using multivariate analysis (quantification II). Results Surface roughness was significantly greater in the DCP group (p < 0.01), and the DCP group members wore their dentures during sleep significantly more often and used a denture cleaner when storing their dentures significantly less often (both p < 0.01). No significant differences were observed for oral cavity dryness or saliva properties. The multivariate analysis showed significant correlations of dental calculi formation with denture surface roughness and items related to denture use and management, but not for oral cavity dryness or saliva properties. Conclusions Our findings indicate that dental calculi formation is influenced by how dentures are used and managed and by denture surface roughness, but not by oral cavity dryness and saliva properties.